Composição corporal e expansibilidade toracoabdominal em idosas praticantes de programa exercício físico supervisionado - Facioli, Tábata Paula; Camargo, Regina Celi Trindade [UNESP]; da Silva, Elaine Aparecida Lozano [UNESP]; da Silva, Juliana Rosini [UNESP]; de Faria, Cláudia Regina Sgobbi [UNESP]; Pinto, Mariana Carvalho [UNESP] (EDIPUCRS, 2015)
Aims: To evaluate the effects of supervised exercise on body composition and thoracoabdominal expansion of women submitted to a regular and supervised exercise program. Methods: Women aged 60 years or older participating in a supervised exercise program, with attendance greater than 75%, were included in the study. The subjects were divided into two groups: exercises twice a week (P2) and three times a week (P3), evaluated before the program and after six months. The circumference measurements during respiratory motion were obtained in the axillary, xiphoid, and umbilical regions, and in the 12th pair of ribs, whereas body composition was assessed by bioimpedance. Results: The sample consisted of 60 elderly women, 29 of whom belonged to P2, with a mean age of 73.93±6.76 years, and 31 to P3, with a mean age of 67.41±5.61 years. Cirtometry demonstrated a higher respiratory coefficient for the 12th pair of ribs in P2 between the beginning (mean 1.94±1.67 cm) and end of the program (mean of 3.07±1.67 cm), p=0.018, and a higher respiratory coefficient in the axillary region in P3 at baseline (mean of 2.17±0.97 cm) and at the end of the program (mean of 2.84±1.81 cm), p=0.030. The other variables remained unchanged. No significant differences were observed when the groups were compared. Regarding body composition, the P2 group had an increase in lean body mass and a decrease in body fat between the beginning and end of the program, while the P3 group maintained the same indices. Conclusions: The elderly women revealed some improvement in thoracoabdominal expansion, increase in lean body mass, and a decrease or maintenance of body fat after six months in the supervised exercise program, with sessions twice or three times a week.
Body composition and thoracoabdominal expansion in elderly women submitted to a supervised physical exercise program
Keywords: Body composition; Exercise; Health of the elderly; Physical